Placebo analgesia and nocebo hyperalgesia in patients with Alzheimer disease and healthy participants - Matthiesen, Susan Tomczak; Sieg, Mette; Andersen, Stephanie Skøtt; Amanzio, Martina; Finnerup, Nanna Brix; Jensen, Troels Staehelin; Gottrup, Hanne; Vase, Lene (Pain (Amsterdam), 2024)
Supplemental Digital Content is Available in the Text. AbstractThe role of placebo analgesia and nocebo hyperalgesia in patients with Alzheimer disease (AD) is largely unknown, with only few studies in the area. Therefore, this study aims to investigate to which extent placebo analgesia and nocebo hyperalgesia effects are present in patients experiencing mild-to-moderate AD. Twenty-one patients with AD (test population) and 26 healthy participants (HP; design validation) were exposed to thermal pain stimulation on 3 test days: Lidocaine condition (open/hidden lidocaine administration), capsaicin condition (open/hidden capsaicin administration), and natural history (no treatment), in a randomized, within-subject design. Open lidocaine and open capsaicin were accompanied by verbal suggestions for pain relief and pain increase, respectively. Expected pain and actual pain intensity were measured on a numerical rating scale (0-10). Placebo and nocebo effects were calculated as pain differences in open-hidden lidocaine and capsaicin, respectively, controlled for no treatment. Healthy participants obtained a placebo effect (P = 0.01) and a trend for a nocebo effect (P = 0.07). Patients with AD did not obtain a placebo effect (P = 0.44) nor a significant nocebo effect (P = 0.86). Healthy participants expected lower and higher pain with open vs hidden lidocaine and capsaicin, respectively (P < 0.001). The same expectation effects were seen in patients with AD (open vs hidden lidocaine, P = 0.008; open vs hidden capsaicin, P < 0.001). With a well-controlled experimental setting, this study suggests that patients with AD may not experience placebo analgesia effects. Nocebo hyperalgesia effects in patients with AD needs further research. These findings may have implications for the conduction of clinical trials and the treatment of patients with AD in clinical practice.